Pengaruh Keseimbangan Kehidupan Kerja, Stres Kerja, Dan Dukungan Sosial Terhadap Kepuasan Kerja Guru (Studi Kasus Pada Guru ASN SMPN & SMAN di Kecamatan Sumberpucung Kabupaten Malang) - Prasasti, Novi Aprilia; Pardiman, Pardiman; Amin, Muhammad Sirojuddin (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract Teachers play a crucial role in developing quality human resources. However, high workloads, administrative demands, and expectations from various parties can cause stress and reduce job satisfaction. The imbalance in the teacher-to-student ratio in Sumberpucung District often requires teachers to teach beyond the minimum hours. Factors such as work-life balance, work stress, and social support are considered to influence teachers' job satisfaction.This study aims to analyze the effect of work-life balance, work stress, and social support on the job satisfaction of civil servant teachers at SMPN and SMAN in Sumberpucung District. This research is causal with a quantitative approach. The population consisted of 143 civil servant teachers, and 105 respondents were selected using the Slovin formula. The sampling technique employed purposive sampling with criteria of married teachers, a minimum of 2 years of work experience, and a teaching load of at least 24 hours per week. Data were collected via questionnaires and analyzed using multiple linear regression with SPSS. The t-test results indicate that work-life balance and social support significantly affect job satisfaction, while work stress does not. The F-test shows that all three variables simultaneously influence job satisfaction. The Adjusted R² value of 0.203 indicates that the independent variables explain 20.3% of the variation in job satisfaction, while the remaining 79.7% is influenced by other factors. Keywords: Work-Life Balance, Job Stress, Social Support, Job Satisfaction